Analisis Historis Kebijakan Ekonomi Orde Baru dan Dampaknya terhadap Transformasi Struktur Perekonomian Indonesia (1966-1998) - Muhammad Rizalul Umam; Muhammad Bagas Riyanto; Shofwatul Mala; Muhammad Rafi Rafsanjani; Hanny Syifa Fauziyah (Universitas Negeri Semarang, 2025)
This study aims to analyze the economic policies of the New Order in a historical context and assess their impact on Indonesia's economic transformation during the period 1966–1998. Starting from the acute economic crisis at the end of the Old Order, marked by extreme inflation, fiscal deficits, and the decline of the agricultural and industrial sectors, the New Order government implemented a series of stabilization and development policies coordinated by technocratic economists. This study employs a descriptive qualitative method, incorporating a literature review approach, and follows Kuntowijoyo's historical research stages, which include heuristics, source criticism, interpretation, and historiography. The contribution of this research lies in its holistic mapping of the dynamics of New Order economic policy, from the stabilization phase through oil-boom-based development expansion, export-oriented industrialization, to the 1997 Asian financial crisis, which marked the collapse of this development model. The results of the study show that Indonesia's economic transformation from agriculture to industry and services has successfully driven high growth, macroeconomic stability, and increased food production. However, this success was built on a fragile foundation, including dependence on oil, foreign capital, foreign debt, and weak economic institutions. This study emphasizes that sustainable development requires institutional reform and economic strategies that are not only growth-oriented but also environmentally and socially responsible.